Communication research in Trujillo-Peru (2011-2015): criteria of the methodological strategy of thesis, according to the Vassallo methodological model. - Carrión Ponce de León, Robert (2017)
The research analyses the nature of the scientific production of communication in the city of Trujillo (Peru), abundant and unknown production. The major aim is to identify and descript characteristics of the epistemological, methodological and operational criteria which influence in the methodologic strategy of undergraduate dissertation of communication of local universities (2011-2015). Using the Qualitative Content Analysis method, the implicit and predominant influence of Positivist Paradigm and Functional Theory and Uses and Gratifications as particular theories was determinate, although without epistemological reflection or a strong mastery of theory. Also, the supremacy of the statistical method, survey andquestionnaire was observed; but exist a lack of conceptual explanation of it. Finally, it identifies companies as the main users of the research results; in this way the necessary social relevance of all study in the context of inequality in Latin America is losing.